Catalyst Luminescence Exploited as an Inherent In Situ Probe of Photoredox Catalysis. Issue 2 (22nd October 2019) - Hayne, David J.; Mohapatra, Sudip; Bawden, Joseph C.; Adcock, Jacqui L.; Barbante, Gregory J.; Doeven, Egan H.; Fraser, Catherine L.; Connell, Timothy U.; White, Jonathan M.; Henderson, Luke C.; Francis, Paul S.
Abstract: The luminescence of commonly used photoredox catalysts offers a continuous inherent in situ probe of electron or energy transfer that can be monitored by photodetectors such as a CCD spectrometer or a digital camera. This approach was applied with complementary ex situ experiments to examine the aerobic oxidation of anthracene with tris(2, 2′‐bipyridine)ruthenium(II) as the catalyst. The reaction results in the precipitation of an isometrically pure syn ‐tetraepoxide not seen in prior studies when an organic photocatalyst was employed. Changes in the emission were observed not only upon electron/energy transfer quenching of the catalyst but also from the presence of particles (undissolved substrate and precipitated product). These features impart dissimilar spectral distributions that can be discriminated by their relative contributions to the RGB data of the digital images. The approach thus enables interrogation of multiple facets of the reaction for monitoring and optimization, and offers unique insight into the mechanisms of photoredox catalysis systems. Abstract : Capturing the light : Monitoring photoredox catalysis systems with a simple photodetector such as a miniaturized spectrometer or a digital camera reveals the timeframe of key electron/energy transfer quenching events and the dissolution and precipitation of solids. This approach is applied to the aerobic oxidation of anthracene with tris(2, 2′‐bipyridine)ruthenium(II) as the catalyst, which yields an isometrically pure syn ‐tetraepoxide.